Penerapan Teknik Intonasi Lagu Mauliate Di Ho O Tuhan Koor Ama Judika pada Ibadah Minggu di Gereja HKBP Nagasaribu IV Resort Nagasaribu Tahun Pembelajaran 2023/2024 - Togi P. Nababan; Robert KA Simangunsong; Roy Josep Hutagalung (Abstrak : Jurnal Kajian Ilmu seni, Media dan Desain, 2024)
This research aims to determine singing techniques in ama choir (men's choir) starting from body posture, breathing, articulation, phrasing and intonation. This research focuses on the application of vocal intonation techniques with the aim of improving singing ability so that you can reach the high and low notes in songs. The method used in this research stage is descriptive qualitative method. The research stages carried out in collecting data were: observation, documentation, video and interviews. The object of this research is the members of the Judika choir at HKBP Nagasaribu IV, totaling 25 people, divided into tenor one, 8 people, tenor two, 7 people, bass one, 5 people, and bass two, 5 people. In the implementation process, researchers held six meetings providing material and singing practice according to correct vocal technique. The results of this research show that the application of intonation techniques in the Judika choir greatly influences and improves the quality of the choir's singing, where members of the Judika choir are more relaxed and relaxed in reaching the high and low notes of the song being sung. Based on this research, it is recommended that you continue to sing using correct intonation so that the quality of the choir increases and can become an example for other ama (men's choirs).